Distribution of lag-1 Alleles, ORF7, and ORF8 Genes of Lipopolysaccharide and Sequence-Based Types Among Legionella pneumophila Serogroup 1 Isolates in Japan and China - Jiang, Luxi; Amemura-Maekawa, Junko; Ren, Hongyu; Li, Yinan; Sakata, Miho; Zhou, Haijian; Murai, Miyo; Chang, Bin; Ohnishi, Makoto; Qin, Tian (Frontiers in Cellular and Infection Microbiology, 2019)
Approximately 85% of cases of Legionnaires’ disease are caused by Legionella pneumophila serogroup 1. In this study, we analyzed the distribution of lag-1 alleles, and ORF 7 and ORF 8 genes of lipopolysaccharide (LPS) and sequence-based types of 616 L. pneumophila serogroup 1 strains isolated in Japan (206 clinical, 225 environmental) and China (13 clinical and 172 environmental). The lag-1 gene was harbored by significantly more of the clinical isolates compared with the environmental isolates (90.3% vs. 19.1% and 61.6% vs. 3.0%, respectively; both P < 0.001). ORF 7 genes were detected in 51.0% of Japanese clinical and 36.0% of Japanese environmental (P = 0.001) isolates, as well as 15.3% of Chinese clinical and 9.9% of Chinese environmental isolates (P = 0.544). ORF 8 genes were detected in 12.1% of Japanese clinical and 5.8% of Japanese environmental (P = 0.017) isolates, as well as 7.7% of Chinese clinical and 3.4% of Chinese environmental isolates (P = 0.388). The Japanese and Chinese isolates were assigned to 203 and 36 different sequence-types (ST), respectively. ST1 was predominant. Most isolates with the same ST also had the same lag-1, ORF 7 and ORF 8 gene subgroups. In conclusion, the lag-1 was present in most of the clinical isolates, but was absent from most of the environmental isolates from both China and Japan, regardless of the water source and SBT type. PCR-based serotyping and subgrouping methods can be used to define a hierarchy of virulence genotypes that require stringent surveillance to prevent human disease.